Insights Into the Prevalence and Impacts of Phthalate Esters in Aquatic Ecosystems - Baloyi, N. D.; Tekere, M.; Maphangwa, K. W.; Masindi, V. (Frontiers in Environmental Science, 2021)
Phthalate esters (PEs) are by far the most produced, and extensively used synthetic organic chemicals with notable applications in many industrial products such as vinyl upholstery, adhesives, food containers, packaging materials, inks, adhesives, cosmetics, paints, pharmaceuticals munitions, and insecticides among other. PEs have long been recognised as ubiquitous organic pollutants of prime environmental concern, with urbanisation amongst the main cause and source of these compounds. Due to their notoriety, these compounds are known to pose devastating effects to living organisms including humans. The presence of PEs and their metabolites in the aquatic ecosystems is of concern primarily due to their endocrine disrupting and carcinogenicity properties. Several research studies have reported prevalence, exposure pathways, toxicity, and impacts of PEs in aquatic ecosystems and humans. Their principal routes of exposure could be direct or indirect, of which, the direct route include contact, eating, and drinking contaminated foods, and the indirect route constitute aerosols, leaching and other forms of environmental contamination. PEs find way into water systems through means such as effluent discharges, urban and agricultural land runoff, leaching from waste dumps, and other diffuse sources.. High-end instrumentation and improved methodologies on the other hand have resulted in increased ability to measure trace levels (μg/L) of PEs and their metabolites in different matrices and ecological compartments of water or aquatic ecosystems lakes, oceans, rivers, sediments, wetlands and drinking water samples. In light of the above, this article provides an informed overview of the prevalence of phthalate esters in aquatic systems and related effects on living organisms and humans. Furthermore, techniques which are commonly used for the extraction and analysis of these PEs are also explained. Future research outlooks and needs are also highlighted in this manuscript. This information will be used to better understand their temporal and spatial distributions in the aquatic systems and aid in devising prudent means to curtail their ecological footprints.